Building Student Confidence and Achievement Through Music Activities at Pcms Kemang Pratama - Vienona Habibah; Dian Herdiati; Hery Budiawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of music education at Purwa Caraka Music Studio (PCMS) Kemang Pratama in enhancing students' self-confidence and achievement. The process of self-actualization in each individual requires a strong sense of confidence, which in turn encourages them to take on new challenges and strive for greater accomplishments in the future. This research employs a qualitative approach, with interviews used as the primary data collection method. The informants in this study consist of three individuals, comprising both teachers and students at PCMS Kemang Pratama. The findings reveal that musical activities which allow students the freedom to choose roles or instruments they are genuinely interested in have a significantly positive impact. Students are more motivated to develop their full potential, which often leads to a consistent record of achievement throughout their learning journey. Moreover, these achievements in turn serve as a powerful reinforcement for their self-confidence. Furthermore, the programs at PCMS Kemang Pratama-particularly those that offer students opportunities to perform on stage based on their interests and talents-have proven effective in fostering a strong sense of confidence. The structured yet flexible learning environment provided by the studio enables students to express themselves authentically while building performance skills and resilience.